Effect of Chronic Kidney Disease on the Renal Secretion via Organic Anion Transporters 1/3: Implications for Physiologically‐Based Pharmacokinetic Modeling and Dose Adjustment. Issue 3 (13th June 2022) - Tan, Shawn Pei Feng; Scotcher, Daniel; Rostami‐Hodjegan, Amin; Galetin, Aleksandra
Abstract : There is growing evidence that active tubular secretory clearance (CLs ) may not decline proportionally with the glomerular filtration rate (GFR) in chronic kidney disease (CKD), leading to the overestimation of renal clearance (CLr ) when using solely GFR to approximate disease effect on renal elimination. The clinical pharmacokinetic data of 33 renally secreted OAT1/3 substrates were collated to investigate the impact of mild, moderate, and severe CKD on CLr, tubular secretion and protein binding ( f u, p ). The f u, p of the collated substrates ranged from 0.0026 to 1.0 in healthy populations; observed CKD‐related increase in the f u, p (up to 2.7‐fold) of 8 highly bound substrates ( f u, p  ≤ 0.2) was accounted for in the analysis. Use of prediction equation based on disease‐related changes in albumin resulted in underprediction of the CKD‐related increase in f u, p of highly bound substrates, highlighting the necessity to measure protein binding in severe CKD. The critical analysis of clinical data for 33 OAT1/3 probes established that decrease in OAT1/3 activity proportional to the changes in GFR was insufficient to recapitulate effects of severe CKD on unbound tubular secretion clearance. OAT1/3‐mediated CLs was estimated to decline by an additional 50% relative to the GFR decline in severe CKD, whereas change in active secretion in mild and moderate CKD was proportional to GFR. Consideration of this additional 50% decline in OAT1/3‐mediated CLs is recommended for physiologically‐based pharmacokinetic models and dose adjustment of OAT1/3 substrates in severe CKD, especially for substrates with high contribution of the active secretion to CLr .